KEMANDIRIAN ANAK TUNAGRAHITA RINGAN MELALUI PEMBELAJARAN TERPADU - Wuryani Wuryani (Perspektif Ilmu Pendidikan, 2011)
The purpose of this study was to discover the application of integrated instruction in improving the independence of mentally retarded students such as in self-cleaning skill, eating and drinking skills, grooming skills and self-danger avoided skills. The method used ini this study was action research, combining qualitative and quantitative paradigms as introduced by Spreadly. The research was conducted in SLB/B, Asih Budi, in South Jakarta as from February through April 2005. After two cycles of treatment, the research found that the integrated instruction can strengthen and improve the independence of mentally retarded students.